2023
DOI: 10.1038/s41421-022-00504-0
|View full text |Cite
|
Sign up to set email alerts
|

A RIPK3-independent role of MLKL in suppressing parthanatos promotes immune evasion in hepatocellular carcinoma

Abstract: Mixed lineage kinase domain-like (MLKL) is widely accepted as an executioner of necroptosis, in which MLKL mediates necroptotic signaling and triggers cell death in a receptor-interacting protein kinase 3 (RIPK3)-dependent manner. Recently, it is increasingly noted that RIPK3 is intrinsically silenced in hepatocytes, raising a question about the role of MLKL in hepatocellular carcinoma (HCC). This study reports a previously unrecognized role of MLKL in regulating parthanatos, a programmed cell death distinct f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…For example, MLKL, a necroptosis regulator, plays complex but little-known roles in cancer development and metastasis 46 , and was recently reported that it can promote immune evasion in HCC 47 . High expression of MAOA was reported to be associated with immunosuppressive tumor microenvironment and poor prognosis 48 .…”
Section: Resultsmentioning
confidence: 99%
“…For example, MLKL, a necroptosis regulator, plays complex but little-known roles in cancer development and metastasis 46 , and was recently reported that it can promote immune evasion in HCC 47 . High expression of MAOA was reported to be associated with immunosuppressive tumor microenvironment and poor prognosis 48 .…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, inhibiting necroptosis reduced tumor-cell-induced endothelial necroptosis, tumor cell extravasation, and metastasis (Strilic et al, 2016). Loss of MLKL may also protect against immune evasion in hepatocellular carcinoma by suppressing parthanatos (Jiang et al, 2023), a cell death mode that occurs following the overactivation of the DNA repair enzyme poly(ADP-ribose) polymerase 1 (PARP1) (David et al, 2009; Yu et al, 2006). Unexpectedly, the deletion of RIPK3 in mouse embryonic fibroblasts dramatically suppressed reprogramming into induced pluripotent stem cells (iPSCs), likely by reducing the expression of cell cycle progression genes (Al-Moujahed et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In support of this, a recent study reported epigenetic silencing of Ripk3 in hepatocytes of a MASH-inducing diet mouse model [ 45 ]. Liver cancer cells are also shown to prevent MLKL-mediated necroptosis by epigenetic silencing of Ripk3 [ 46 ]. Surprisingly, in our study, Mlkl −/− mice on the HFHFrHC diet exhibited elevated levels of TNFα, IL6, IL1β, and Ccl2 in the liver, challenging previous data indicating that MLKL deficiency reduces inflammation [ 23 , 44 ].…”
Section: Discussionmentioning
confidence: 99%